Nitrogen‐Doped Carbon Enables Heterogeneous Asymmetric Insertion of Carbenoids into Amines Catalyzed by Rhodium Nanoparticles - Masuda, Ryusuke; Yasukawa, Tomohiro; Yamashita, Yasuhiro; Kobayashi, Shū (Angewandte Chemie International Edition, 2021)
Development of stable heterogeneous catalyst systems is a crucial subject to achieve sustainable society. Though metal nanoparticles are robust species, the study of asymmetric catalysis by them has been restricted because methods to activate metal nanoparticles without causing metal leaching were limited. We developed Rh nanoparticle catalysts (NCI‐Rh) supported on nitrogen‐doped carbon as a solid ligand to interact with metals for asymmetric insertion of carbenoids into N−H bonds cocatalyzed by chiral phosphoric acid. Nitrogen dopants played a crucial role in both catalytic activity and enantioselectivity while almost no catalysis was observed with Rh nanoparticles immobilized on supports without nitrogen dopants. Various types of chiral α‐amino acid derivatives were synthesized in high yields with high enantioselectivities and NCI‐Rh could be reused in seven runs. Furthermore, we demonstrated the corresponding continuous‐flow reaction using a column packed with NCI‐Rh. The desired product was obtained efficiently for over 90 h through the reactivation of NCI‐Rh and the chiral source could be recovered. Rh nanoparticle catalysts supported on nitrogen‐doped carbon were developed for asymmetric insertions of carbenoids derived from diazoesters into N−H bonds cocatalyzed by chiral phosphoric acid. The nitrogen dopants are essential to promote the reactions. The catalyst could be reused several times and was applicable for a continuous‐flow reaction system that produced the desired chiral amine for over 90 h through reactivation of the catalyst.